Whole Farm, Profit Objective Pricing - Langemeier, Micheal R. (My University, 2003)
This publication is meant to help producers calculate a profit objective price for their commodities in any given year based on that year's farm mix of crops and livestock and on historical price and production data.
MF1101_2003_10
Keywords: MF1101; Economics; MF